CX3CL1-Fc treatment prevents atherosclerosis in Ldlr KO mice - Matthew Riopel; Melanie Vassallo; Erik Ehinger; Jennifer Pattison; Karen Bowden; Holger Winkels; Maria Wilson; Ron de Jong; Sanjay Patel; Deepika Balakrishna; James Bilakovics; Andrea Fanjul; et al. (Elsevier, 2019)
Objective: Atherosclerosis is a major cause of cardiovascular disease. Monocyte-endothelial cell interactions are partly mediated by expression of monocyte CX3CR1 and endothelial cell fractalkine (CX3CL1). Interrupting the interaction between this ligand-receptor pair should reduce monocyte binding to the endothelial wall and reduce atherosclerosis. We sought to reduce atherosclerosis by preventing monocyte-endothelial cell interactions through use of a long-acting CX3CR1 agonist. Methods: In this study, the chemokine domain of CX3CL1 was fused to the mouse Fc region to generate a long-acting soluble form of CX3CL1 suitable for chronic studies. CX3CL1-Fc or saline was injected twice a week (30 mg/kg) for 4 months into Ldlr knockout (KO) mice on an atherogenic western diet. Results: CX3CL1-Fc-treated Ldlr KO mice showed decreased en face aortic lesion surface area and reduced aortic root lesion size with decreased necrotic core area. Flow cytometry analyses of CX3CL1-Fc-treated aortic wall cell digests revealed a decrease in M1-like polarized macrophages and T cells. Moreover, CX3CL1-Fc administration reduced diet-induced atherosclerosis after switching from an atherogenic to a normal chow diet. In vitro monocyte adhesion studies revealed that CX3CL1-Fc treatment caused fewer monocytes to adhere to a human umbilical vein endothelial cell monolayer. Furthermore, a dorsal window chamber model demonstrated that CX3CL1-Fc treatment decreased in vivo leukocyte adhesion and rolling in live capillaries after short-term ischemia-reperfusion. Conclusion: These results indicate that CX3CL1-Fc can inhibit monocyte/endothelial cell adhesion as well as reduce atherosclerosis. Keywords: Fractalkine, CX3CR1, Atherosclerosis, Monocyte adhesion, Inflammation, Ldlr KO